(untitled) (MAUSAM, 1971)
The quasi-geostrophic omega equation has been numerically solved to get the vertical velocity distribution in a typical westerly disturbance. The effects of sensible heat and latent heat of condensation are also for a 4-layer model. The computations were performed on HITAC 5020. The numerically obtained vertical velocity field is in good agreement with the observed weather pattern associated with the middle latitude large-scale disturbance, i.e., ascending motion in front of the trough and downward motion in the rear of the trough.